The Effect of Dependence on Cell Phones on the Mental Health of Prospective Teachers - Ali, Muhammad (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
Mental health is a vital condition for a person because it can affect every aspect of their life. However, mental health does not escape the factors that affect it. One factor that can affect mental health is the use of mobile phones. For aspiring teachers, mobile phones have become integral to their daily activities. However, various studies have found that dependence on mobile phones can hurt a person's mental health. This study aims to analyze the impact of dependence on mobile phones on the mental health of prospective teachers, dimensions of mental health, and aspects of mental health influenced by dependence on mobile phones. This study used a correlational quantitative method. Data was collected through questionnaires distributed to 231 PAI IAIN Ponorogo students—data analysis using simple linear regression. The results showed that there was an effect of dependence on mobile phones on mental health, with an influence of 19%. Dependence on cell phones also affects psychological distress but does not affect psychological well-being. Moreover, it affects anxiety, depression, uncontrollable emotions, and life satisfaction but does not affect positive feelings and emotional bonding.